- PERLINDUNGAN INDIKASI GEOGRAFIS MOKE AIMERE : - - Matheus Surya Pribadi Wadapone; Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2024)
A cultural heritage product, Moke Aimere has a close connection with the community and geographical conditions in Aimere District. The people of Aimere hope that Moke Aimere can be protected or registered as a Geographical Indication, considering that currently many other parties are using the name